Investigation of shallow marine Antarctic environments using the annual increment growth pattern of the bivalve mollusc Aequiyoldia eightsii (Jay, 1839). - Roman-Gonzalez, Alejandro (2017)
The research presented here constitutes the latest advances in the use of the Antarctic bivalve mollusc Aequiyoldia eightsii as a sclerochronological proxy for Antarctic coastal waters. A. eightsii has the potential to provide annually-resolved records for the Antarctic shallow waters beyond the beginning of the instrumental record. A comprehensive study of A. eightsii shell growth was carried out, which highlighted two ontogenetic trends: i) negative exponential and ii) a quasi-cyclic trend of a period of nine years, which may relate to allocation of energetic resources. Using crossmatching techniques, four chronologies from adjacent locations near Rothera Station (West Antarctic Peninsula, WAP) and an additional chronology from historical samples collected near Signy Station (South Orkney Islands, SOIs) were developed. Additionally further work on a pre-existing chronology from the SOIs is presented. Instrumental records and climatic indices were analysed to determine environmental variability and the factors controlling shell growth. Seawater temperature and fast-ice duration seem to be the main environmental drivers of A. eightsii shell growth. Shell growth of South Cove (WAP) specimens seem to better reflect to environmental conditions recorded in the Rothera Biological Time Series. Stable oxygen and carbon isotope (δ18O and δ13C) records were developed from shell carbonate material; these showed sub- and inter-annual variability and all specimens showed similar trends in δ18Oshell and δ13Cshell, with the exception of a deep-collected specimen of the SOIs, which showed much reduced interannual variability and a stronger δ13Cshell negative trend with ontogenetic age. Additionally, stable isotope fractionation depending anatomical part of the shell (anterior, ventral and posterior) was studied, which showed intra-increment variability in δ18Oshell and δ13Cshell. The present work constitutes a comprehensive calibration of A. eightsii as a sclerochronological proxy for Antarctic shallow coastal waters, which ...